Penerapan Budaya Kearifan Lokal di Era Trend Budaya K-Pop Melalui Pendidikan Kewarganegaraan - Olipian Resky Pernando; Nur Azizah; Ilham Hudi; Ilma Amelia; Evi Suryani; Sri Cahyani (International Forum of Researchers and Lecturers, 2024)
This research aims to analyze the impact of K-pop cultural trends on local culture in the context of citizenship education in the era of globalization. The method used is a Systematic Literature Review (SLR) by collecting 60 articles from Google Scholar in 2019-2023, which examine the influence of K-pop and the role of citizenship education in maintaining local cultural identity while accommodating global popular culture. The results of this research propose the integration of local cultural wisdom into the educational curriculum, with the aim of developing a balanced understanding of local and global culture, as well as preserving cultural heritage in a dynamic modern context. The findings of this study highlight the importance of local wisdom values ​​in education to strengthen students’ cultural identity in the era of globalization.